Endangered amphibians infected with the chytrid fungus Batrachochytrium dendrobatidis in austral temperate wetlands from Argentina - Ghirardi, Romina (2014)
Infections caused by the chytrid fungus Batrachochytrium dendrobatidis (B.d.) have been highlighted as one of the driver of worldwide amphibians declines. In austral temperate wetlands of South America, the anuran diversity is particularly exposed to stressors that can increase the potential negative effect of emerging infectious diseases. We assessed the presence of B.d. infecting anurans from different environments in Patagonia through molecular analysis of skin swabs from 122 individuals belonging to six species. We reported B.d. in four species, two of which are categorized as endangered, and extended the known distribution of the fungus to new areas. Based on our result, we consider that two of the species we studied deserve particular conservation attention: Atelognathus patagonicus and Alsodes pehuenche. The populations of these species should be monitored and special conservation efforts should be directed to protect them.